British Regional Heart Study: geographic variations in cardiovascular mortality, and the role of water quality. Issue 6226 (24th May 1980) - Pocock, S J; Shaper, A G; Cook, D G; Packham, R F; Lacey, R F; Powell, P; Russell, P F
Abstract : In a study of regional variations in cardiovascular mortality in Great Britain during 1969-73 based on 253 towns the possible contributions of drinking water quality, climate, air pollution, blood groups, and socioeconomic factors were evaluated. A twofold range in mortality from stroke and ischaemic heart disease was apparent, the highest mortality being in the west of Scotland and the lowest in south-east England. A multifactorial approach identified five principal factors that substantially explained this geographic variation in cardiovascular mortality—namely, water hardness, rainfall, temperature, and two social factors (percentage of manual workers and car ownership). After adjustment for other factors cardiovascular mortality in areas with very soft water, around 0·25 mmol/l (calcium carbonate equivalent 25 mg/l), was estimated to be 10-15% higher than that in areas with medium-hard water, around 1·7 mmol/l (170 mg/l), while any further increase in hardness beyond 1·7 mmol/l did not additionally lower cardiovascular mortality. Thus a negative relation existed between water hardness and cardiovascular mortality, although climate and socioeconomic conditions also appeared to be important influences. Cross-sectional and prospective surveys of 7500 middle-aged men from 24 towns are in progress and will permit further exploration of these geographic differences, especially with regard to personal risk factors such as blood pressure, blood lipid concentrations, and cigarette smoking.